Correlation of Radiographic Parameter with Functional Outcomes in Pediatric Supracondylar Humerus Fractures (SCHF) Treated with Close Reduction and Percutaneus Pinning (CRPP) - Irsan Kesuma (Journal of Global Pharma Technology, 2016)
Background Humerus supracondylar fracture is one of the most common elbow injuries and this injury approximately includes 16.6 % of all fractures in children(1). Until now, one of the current treatment for a displaced supracondylar humeral fracture is closed reduction of  the fracture is using the percutaneous skeletal fixation(4). The Baumann angle and Carrying angle  of the humerus has been a commonly used as an outcome measure for supracondylar fractures in children(6,7). The aim of this study was to evaluate the radiographic parameter with functional outcomes in pediatric Supracondylar Humerus Fractures (SCHF) treated with CRPP. Materials and Method This was a cross sectional observational study conducted on a consecutive series of supracondylar humerus fracture patients. It involved patients in Sardjito General hospital that were diagnosed as supracondylar humerus fracture treated with close reduction percutaneous pinning. Several parameters were reviewed, including Bowmann angle, Carrying angle, age at injury, sex, right or left extremity, Gartland fracture type, mechanism of injury, operative or nonoperative treatment intervention. Then, the functional outcome of the subjects in this study was measured using QuickDASH score which is the short form of  DASH score. Chi Square test and Independent T Test was using as the statistical analysis for this study. Result This study included 78 out of 104 supracondylar humeral fractures. 26 patients were excluded from this study. Out of 78 patients, 25 (32%) were in girls and 53 (68%) were in boys. The mean duration of follow-up all patients was 35 months. During the first data-collection, the mean Baumann angle of the humerus was found to be 72.76 ° (range 55.00 ° to 87.00 °, SD 6.17 °) . This was not significantly different from the data obtained during the second data-collection (mean 72.98 °, range 65° to 80 °, SD 6.21 °). Carrying angle pre operatively was found (mean 10.80 °, range 2 ° to 17°, SD 3.12 °). And not significantly different from post operatively (mean 10.94 °, range 2° to 18 °, SD 3.23 °). There was  no functional interference with normal social activities, sports performing, and a activities of daily living, and no functionally limiting symptoms Conclusion This study showed that good functional outcome with better carrying angle was achieved in patient with SCHF patients treated with CRPP.